SOME QUESTIONS OF ORGANIZATIONAL AND LEGAL ASPECTS OF HOTEL SERVICES IN THE TERMS OF COVID-19 - Shukhrat Nuralievich Ruzinazarov, Nilufar Khodji-Akbarovna Rakhmonkulova, Liliya Ilkhomovna Achilova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The tourism sector is most acutely affected by the spread of COVID-19 in the world. The closure of the external and internal borders this year not only reduced the revenues of tourism companies to zero, but also led in some cases to the bankruptcy of hotel, transport, as well as catering, sightseeing and consulting services in the tourism sector. Resolute measures have been taken to contain the spread of the virus in Uzbekistan, as well as to mitigate the socio-economic consequences of the pandemic. The crisis in the tourism sector will be largely neutralized by strengthening public-private partnerships at all levels in order to restore and negatively impact tourism.